New Organo Soluble and Thermally Stable Schiff Base Polymers by Oxidative Polycondensation - OZBULBUL, ASLI; TUNCEL, MEHMET; SERIN, SELAHATTIN (Asian Journal of Chemistry, 2010)
The Schiff base monomer was synthesized by the condensation reaction between salicyladehyde and p-phenylendiamine. The Schiff base polymers having double azomethine group were prepared by oxidative polycondensation (OP) reaction of monomer in aqueous alkaline medium with NaOCl (P1) and H2O2 (P2) as the oxidants at 90 ºC. Cu(II) and Ni(II) complexes of the polymers were synthesized by the reaction of polymer and metal-acetate salts. The monomer and polymers were characterized by elemental analyses, thermogravimertic analyses, DSC analyses, UV-Vis, FT-IR, 1H and 13C NMR spectroscopic studies, which revealed that the P1 and P2 polymers synthesized by OP is composed of oxyphenylene (C-O-C; P1 = 77 %, P2 = 75 %), phenylene (C-C; P1 = 23 %, P2 =25 %) units. Average molecular weights of polymers were determined by gel permeation chromatography. The polymers were soluble in polar aprotic solvents and aqueous alkaline media. According to the thermogravimetric analyses, Schiff base polymer (P2) exhibited excellent thermal stability with 38 % residual weight at 1000 ºC in nitrogen atmosphere. The thermal stability of these polymer systems are found to be in order P2 > P1. As the synthesized polymers were soluble in common solvents such as THF, DMF, DMSO, these properties of polymer are promising for it is environmental and analytical usage.